Methods for Representing Earthquake Time Series with Networks (Informatica, 2024)
An earthquake is a natural phenomenon that occurs as a result of the internal dynamics of the Earth. It originates deep below the surface of the planet and cannot be predicted with our current knowledge. In this paper, we use a network analysis approach to analyze the characteristics and evolution of seismic activity over time. We implement several network models based on temporal and spatial interactions between earthquakes and on the assumption of self-similarity of seismic activity in selected geographic areas. We create sequences of networks generated in consecutive time windows and compare the networks between different models and time intervals. Additionally, we calculate a set of network structural characteristics and study their changes over time. The analysis shows that most models produce networks with such a structure that changes consistently with the intensity of seismic activity. Thus, based on the structural changes of networks, we can reliably identify the time windows with increased seismic activity.